Current Controller with FOPI Modification for VSI-based Active Power Filter - Tyas Prasetyo, Antonius Doddy; Dery Elfando; Silalahi, Eva Magdalena (Universitas Muhammadiyah Surakarta, 2025)
The integration of photovoltaic (PV) systems into the grid, combined with nonlinear loads and bidirectional power flows, significantly impacts grid voltage stability and total harmonic distortion (THD) in low-voltage distribution systems. This study proposes the application of an Active Power Filter (APF) to improve power quality (PQ) and mitigate harmonic distortion caused by nonlinear loads. Harmonic distortion from nonlinear loads poses a substantial risk of damaging electronic equipment and degrading overall power quality. The proposed APF utilizes a Fractional Order Proportional-Integral (FOPI) controller implemented through a Voltage Source Inverter (VSI). The effectiveness of the FOPI controller was evaluated through simulation and compared to a conventional PI controller. The results demonstrate that the FOPI-controlled system successfully reduces current THD to meet IEEE 519 standards (< 5%), highlighting the superior performance and robustness of the FOPI controller compared to traditional approaches.